Dual functionalized natural biomass carbon dots from lychee exocarp for cancer cell targetable near-infrared fluorescence imaging and photodynamic therapy. Issue 38 (26th September 2018) - Xue, Mingyue; Zhao, Jingjin; Zhan, Zhihua; Zhao, Shulin; Lan, Chuanqing; Ye, Fanggui; Liang, Hong
Abstract : Dual functionalized natural biomass carbon dots from lychee exocarp were fabricated for cancer cell targetable near-infrared fluorescence imaging and photodynamic therapy. Abstract : Photodynamic therapy (PDT) is a non-invasive phototherapy that has gained significant attention for cancer therapy. However, image-guided PDT still remains a considerable challenge. Herein, we developed a targeted, near-infrared (NIR) fluorescence imaging nanoprobe for cancer cells by preparing natural biomass carbon dots (NBCDs) from lychee exocarp, and loading transferrin and a photosensitizer on the NBCD surfaces for image-guided PDT of cancer cells and mouse tumors. Because the surfaces of cancer cells exhibit more transferrin receptors, the proposed NIR fluorescent nanoprobe can better penetrate cancer cells for cancer cell targetable fluorescence imaging. Thus, the dual-function nanoprobe made from natural biomass can be used as a specific agent for NIR fluorescence imaging and PDT. More importantly, the functional nanoprobe prepared from natural biomass emits NIR fluorescence, shows very low biological toxicity, and can minimize side effects on normal cells. After directly injecting the nanoprobes into tumor tissues, the photosensitizers on the surface of the NBCDs can produce singlet oxygen ( 1 O2 ) through photodynamic reactions when irradiated with 650 nm light to kill cancer cells, thus inhibiting tumor growth in PDT-treated mice. Therefore, the functional fluorescent nanoprobe made from natural biomass has been employed as a PDT agent, and holds great promise in image-guided tumor PDT.